DETERMINAN FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SCOOTER SCOOPY DI KOTA BANJARMASIN - - Mohdari; Penta Lestarini Budiati; J.M. Verawaty Sitorus (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, This study aims to re-examine the factors that influence consumer purchasing decisions for motorbikes with scoopy type in Banjarmasin. The factors used are product quality, price perception, and brand image which are hypothesized to influence the purchase decision of a scoopy scooter. The analysis method used is multiple regression analysis with the help of the SPSS for window version 22 statistical program and hypothesis testing which is guided by if the P value <0.05 then the conclusion is Ha accepted and if P value> 0.05 then Ha is rejected. The results show that there is an influence positive product quality, price perception and brand image on purchasing decisions either partially or simultaneously.